An experimental study on mechanical properties of fiber-reinforced concrete of energy piles - Songying Zhao; Lei Chen; Yan Fu (Fracture and Structural Integrity)
The technology of energy piles for heat storage involves turning the concrete piles buried beneath the ground into a part of the ground-source heat pump system and burying the heat-transfer tubes in the foundation piles, which are regarded as heat transfer wells. The heat transfer tubes are embedded in the concrete foundation piles, destroying the mechanical bearing capacity of the piles and damaging the safety of the buildings. Thus, considering the structural stability and the degree of heat transfer of concrete piles, as well as the selection of material for the foundation piles, the mixing ratio of the material of the energy piles is experimentally studied by the orthogonal method. The optimum mixing ratio of the energy pile is thus obtained. A concrete test block is used to conduct a static load test and splitting test to verify the mixing ratio of the concrete of the energy pile. The results show that steel fiber can be used to enhance the bearing capacity of the storage pile as a reinforcement material. Under a reasonable ratio, the reinforced pile can absolutely meet the original design requirements. Ordinary Portland cement or composite Portland cement can be used as cementitious materials for energy piles. Through an experiment, it is proved that the composite Portland cement can better meet the requirements of the concrete foundation piles than the cementitious material. As thermal conductivity materials, the addition of industrial graphite and scrap copper slag can improve the thermal conductivity of the pile, but it can also reduce the mechanical properties of the pile. It is necessary to control it in a certain range and not to add a large amount of graphite just to improve the thermal conductivity.